The Use of Hangman Game in Motivating Students in Learning English - Manan, Rika Mandasari (Universitas Swadaya Gunung Jati, 2016)
In learning foreign language such as English, a learner should have motivationin order to have willingness to learn. This study is an attempt to investigate thestudents’ motivation in learning English by using Hangman Game. And this study wasto find out if the use of Hangman game motivates the students in learning English. Themethod used in this study was quantitative with experimental research design. Thetarget population of this study was the eighth grade students of MTs Negeri Cirebon 1.The writer took two classes as samples and the number of the samples was 36 students.The samples were divided into experimental group and control group. There are tworesearch instruments which were used to collect data. They were questionnaire andobservation. The result analysis of observation showed that the students in experimentalgroup had higher motivation than in control group. Meanwhile, the calculation of thevalue of the questionnaire showed that there were significant differences betweenexperimental group and control group. The result of taccount was 2,44 while the result ofttable was 1,994. It was mean that the value of taccount (2,44) > ttable (1,994). So,hypotheses alternative (Ha) was accepted or the use of Hangman game motivate thestudents in learning English to eighth grade students of MTs Negeri Cirebon 1.